Apolipoprotein A-I Mimetic Peptide L-4F Suppresses Granulocytic-Myeloid-Derived Suppressor Cells in Mouse Pancreatic Cancer - Peng, Meiyu; Zhang, Qi; Liu, Yanqing; Guo, Xiangdong; Ju, Jiyu; Xu, Lingzhi; Gao, Yuanyuan; Chen, Daquan; Mu, Dongzhen; Zhang, Rongxin (Frontiers in Pharmacology, 2020)
L-4F is an Apolipoprotein A-I (ApoA-I) mimetic peptide, it was engineered to imitate the anti-inflammatory and anti-oxidative activity of ApoA-I. In this paper, H7 cell was used to construct a mouse model of pancreatic cancer in situ, and the mice were treated with L-4F. Then, the development of pancreatic cancer and myeloid-derived suppressor cells (MDSCs) infiltration were investigated in vivo. After L-4F treatment, the differentiation, proliferation and apoptosis of MDSCs were detected in vitro. Moreover, we test its effects on the immunosuppressive function of MDSCs ex vivo. The results show that L-4F significantly reduced the tumorigenicity of H7 cells. L-4F suppressed granulocytic myeloid-derived suppressor cells (PMN-MDSCs) differentiation and inhibited the accumulation of PMN-MDSCs in the mouse spleen and tumor tissue. L-4F weakened the immunosuppressive function of MDSCs, resulting in decreased production of ROS and H2O2 by MDSCs, and increased T cell proliferation, IFN-γ and TNF-βsecretion, and CD3+CD4+ T and CD3+CD8+ T cell infiltration into the mouse spleen and pancreatic cancer tissue. Furthermore, L-4F significantly down regulated the STAT3 signaling pathway in PMN-MDSCs. These results indicated that L-4F exerts an effective anti-tumor and immunomodulatory effect in pancreatic cancer by inhibiting PMN-MDSCs.